PENGARUH METODE MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN IPAS KELAS IV SD N 120 PALEMBANG - Indriani; Nurlaeli; Muhammad Afandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the effect of the mind mapping method on students' critical thinking skills in the Natural and Social Sciences (IPAS) subject for fourth-grade students at SDN 120 Palembang. The background of this research is based on the low level of students' critical thinking skills, which is attributed to conventional teaching methods that lack active student involvement. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research sample consisted of two classes: Class IV A as the control group and Class IV B as the experimental group, each comprising 30 students. The research instrument was a critical thinking test based on higher-order thinking skills (HOTS) indicators, namely analyzing (C4), evaluating (C5), and creating (C6). The results showed a significant improvement in the critical thinking skills of students in the experimental group after the implementation of the mind mapping method compared to the control group. Thus, the mind mapping method proved to be effective in enhancing students' critical thinking skills in IPAS learning. These findings are expected to serve as a reference for teachers in selecting innovative and appropriate teaching methods to improve the quality of learning in elementary schools.